Avaliação eletrocardiográfica ambulatorial de cães com ehrliquiose monocítica crônica - Filippi, Maurício Gianfrancesco [UNESP] (2016)
Ambulatorial electrocardiographic monitoring, or Holter method, has been shown to be an effective tool in veterinary medicine to detect early heart lesions, not only to monitor the electrical activity of the heart, but also to control the autonomic nervous system of this organ. It is also known that the main infectious diseases of dogs, such as canine distemper and canine monocytic ehrlichiosis (CME) cause considerable lesions in the heart, proven by histopathological examination. It has already been proven the occurrence of myocarditis in the CME, leading to frequent presence of changes in the generation and conduction of the cardiac electrical impulse. The present study analyzed the electrical activity of the heart during 24 hours, focusing on the prevalence of arrhythmias, heart rate variability study and the biomarkers concentration of dogs with chronic CME (sick group) compared to healthy animals (control group). Forty-five percent of the animals in the diseased group had a high frequency of arrhythmias during the study. The mean concentration of cardiac troponin I and creatinokinase MB (CK-MB) was significant (0.24 ng / mL ± 0.5; 229 ± 205 IU / mL) compared to the control group (0.042 ± 0.07 ng / ML, 126 ± 46.12 IU / mL). The standard deviation of the mean of all NN (SDNN) intervals and the percentage of adjacent RR intervals with a duration difference greater than 50 milliseconds (pnn50%) were also extremely significant (83 ± 65 and 14.56 ± 20) when compared to Healthy animals (268 ± 74.6, 55.87 ± 12.8), respectively. It can be concluded that chronic CME has an arrhythmogenic character, where there is persistent myocardial injury and intense stimulation of the sympathetic autonomic nervous system of the heart.